Cyber-Physical Systems-Based PID Controller for Three Interacting Tank Process Level Control. Issue 1 (March 2021) - Joelianto, E; Nadhira, V; Hammami, H; Hariyadi
Abstract: This paper considers the performance improvement of PLC-based process control systems through Industry 4.0 by harnessing cyber-physical systems (CPS), which is an integration of control, computation, and networking to intertwine intensely cyber and physical components. To accomplish these needs, open process control (OPC) unified architecture (UA) is exercised as a horizontal and vertical integrator of the CPS-based process automation. The three interacting tank process is the preferred testing plant because this system has become a proven benchmark for testing advanced control system in the laboratory scale. In this paper, the cyber component accomplishes parameter optimization of the PID controller for the level control of the three interacting tank process and schedules the appropriate PID controller that matches the level operating conditions. The control implementation shows that CPS for the level control of the three interacting tank process works well by resulting in smaller integral square error (ISE) value. Moreover, the cloud-based database can be established directly using OPC UA for real-time monitoring of the process through websites using the Internet network with data delivery rate of 100%.